Pembinaan Perilaku Sopan Santun Berbicara Kepada Teman Sebaya di Desa Wolwal Barat - Adolfina Oualeng; Eunike Molebila; Alboin Selly; Nehemia Fanpada; Milkarno P. Mautukas; Stefanus Maure (Peneliti.net, 2022)
Polite behavior in speaking is a culture of the Indonesian nation, however, the culture of politeness which has been passed down for a long time has begun to disappear. Have started to lose manners in talking to other people or with peers. Disrespectful words are often spoken either between the interlocutor or through the mass media. The availability of information technology through mass media can be misused to speak impolitely either directly or indirectly so that it can disturb the peace, thus this coaching activity is carried out so that people have polite behavior in talking between peers. This coaching activity was carried out in the West Wolwal Village. The preparation of the activities was carried out from October to November 2020 and the activities were carried out in 1 day, namely November 22, 2020. The material presented included: good communication ethics, development of information technology, various impacts of impolite speaking behavior both directly and indirectly. . Questions and answers were held at the end of the activity and there was a commitment from the participants to behave politely in speaking.